General fuzzy finite switchboard automata - Kavikumar, J.; S. P., Tiwari; Ebas, Nur Ain; A. H., Nor Shamsidah (World Scientific Publishing, 2019)
The constructions of finite switchboard state automata are known to be an extension of finite automata in the view of commutative and switching state machines. This research incorporated an idea of a switchboard in the general fuzzy automata to introduce general fuzzy finite switchboard automata. The attained output reveals that a strongly connected general fuzzy finite switchboard automaton is equivalent to the retrievable general fuzzy automata. Further, the notion of the switchboard subsystem and strong switchboard subsystem of general fuzzy finite switchboard automata are examined. Finally, the concept of fuzzy topology on general fuzzy finite switchboard automata in terms of these characterisations is formulated.